Surface covering Robot simulator using Random walk strategy - Benmerzoug, Rima; Supervisor: MOUSSAOUI, Adel (UNIVERSITY of M'SILA, 2022)
This work is a simplified study on the use of random walk strategy in covering 2D spaces on a blind robot simulator. The first chapter is a general introduction to the topic of surface covering, followed by some initial definitions and the importance of surface covering in different areas of life. Then some of the most important methods of coverage, Achieved strategies and algorithms in the second chapter with a simple explanation of two of them, and the second chapter mainly contains the structure of the simulator and its algorithms. Random walking versus distributed random walking strategy as an improvement will also be addressed, perceptions, advantages, and weaknesses. The content of the 3rd and final chapter is the test and results on the emulator application where the reader will reveal the level of effectiveness of this improved algorithm.
Keywords: Surface covering, covering robot, Random walk, robot simulator.